Oxytetracycline Mineralization inside a UV/H2O2 System of Advanced Oxidation Processes: Inorganic By-Product - Anisa Ur Rahmah; Sabtanti Harimurti; Kiki Adi Kurnia; Abdul Aziz Omar; Thanabalan Murugesan (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Oxytetracycline (OTC) was widely used antibiotic in agricultural industry. However, most of them were secreted from the body and entered the water stream, due to low absorption. The occurrence of the antibiotics in water stream may led to serious health hazards. Hence, finding the effective method that capable to achieve total mineralization of antibiotic-contaminated wastewater, followed by the production of benign inorganic and organic by-product, was necessarily deemed. Photochemical degradation method, such as: UV/H2O2 system, was capable to achieve total mineralization of OTC at its optimized condition. In this paper, inorganic by-products of OTC mineralization inside a UV/H2O2 system at its optimum condition were analyzed. The presence of nitrate, ammonium, chloride ions, and chlorine were detected at the sample solution after mineralization. The presence of these inorganic by-product has proven that the experimental setup chosen was capable to achieve total mineralization. In addition, possible routes of the inorganic by-products detachment from the OTC’s structure, were also presented. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).